2017
DOI: 10.24925/turjaf.v5i11.1429-1438.1292
|View full text |Cite
|
Sign up to set email alerts
|

Türkiye'de Kayısı Islah Çalışmaları ve Islah Edilen Yeni Çeşitler

Abstract: Kayısı, güzel renk, tat ve aroması, yüksek A vitamini ve diyet lifi içeriğiyle yaz mevsiminde sevilerek tüketilen meyvelerin başında gelir. İlkbahar geç donlarının neden olduğu kayıplar, farklı iklim koşullarına zayıf adaptasyon, sofralık kayısılarda raf ömrünün kısa olması, şarka ve monilya hastalığının yol açtığı zararlar bugün kayısı yetiştiriciliğinde karşılaşılan en önemli sorunlardır. Son yıllarda tüketici tercihlerinde yaşanan hızlı değişimlere birlikte renk, tat, aroma ve irilik bakımından farklı özell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…The results of the study showed that ITS and LEAFY DNA sequences successfully discriminated the Şalak cultivar from other cultivars. Previous studies have mentioned that "Aprikoz" and "Şalak" are the same cultivars (Asma 2000, Alim & Kaya 2005Asma & Ozturk 2005). However, these cultivars differed according to the DNA sequencing results based on the ITS gene region.…”
Section: Discussionmentioning
confidence: 96%
“…The results of the study showed that ITS and LEAFY DNA sequences successfully discriminated the Şalak cultivar from other cultivars. Previous studies have mentioned that "Aprikoz" and "Şalak" are the same cultivars (Asma 2000, Alim & Kaya 2005Asma & Ozturk 2005). However, these cultivars differed according to the DNA sequencing results based on the ITS gene region.…”
Section: Discussionmentioning
confidence: 96%
“…Turkiye is the leader in fresh apricot production and dried apricot export in the world with a 833,398 tons/year of apricot production (FAO, 2020). Approximately 50% of fresh apricots and 90% of dried apricots are produced in the Eastern Anatolia Region (Abacı & Asma, 2010; Akın et al, 2008; Asma, 2000). Malatya, Igdir and Elazig are the cities in this region for the biggest apricot production of 389.396, 42.989, 31.179 tons/year respectively (TÜİK, 2021).…”
Section: Introductionmentioning
confidence: 99%